TECTONO-PHYSICAL CONDITIONS FOR THE FORMATION OF STRUCTURES OF CENTRAL TYPE, THE PATTERNS OF DISTRIBUTION OF HYDROCARBON DEPOSITS AND FOCI OF EARTHQUAKES - Vladimir Mikhaylovich Kharchenko; Alina Evgenyevna Domareva (Наука. Инновации. Технологии, 2022)
The paper presents a geodynamic conditions of formation of SCT, which is based on law of shear stress [3] and the regularities of distribution of tectonic stresses, outlined in the famous work by M. V. Gzovsky (1975) [2]. The basis for construction of geological-tectonic models of district heating network, which are allocated in the form of «broken plates» is a well-known model of the earthquake source, where the allocated zone of compression and extension, oriented perpendicular to each other. For interpretation of district heating network in accordance with this model vydelyayut also zones of compression and extension, portions of interference and nodal points, the intersection points lineaments and concentric faults of various ranks, which are interpreted as zones of subvertical destruction. The latter are prospective for the discovery of new foci of earthquakes, and a particularly promising objects for the presence of oil and gas.